2022
DOI: 10.3390/ijms23116178
|View full text |Cite
|
Sign up to set email alerts
|

The Pyroptosis-Related Gene Prognostic Index Associated with Tumor Immune Infiltration for Pancreatic Cancer

Abstract: Pancreatic cancer (PC) is one of the most fatal malignancies. Pyroptosis, a type of inflammatory cell death, likely plays a critical role in the development and progression of tumors. However, the relationship between pyroptosis-related genes (PRGs) and prognosis and immunity to PC is not entirely clear. This study, aimed at identifying the key PRGs in PC, highlights their prognostic value, immune characteristics, and candidate drugs for therapies. We screened 47 differentially expressed PRGs between PC and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Conversely, diminished levels of NLRP1 increased the sensitivity of pancreatic cancer cells to ERK inhibitors [46]. Multi-omics analyses further reinforce the prospect of NLRP1 serving as a biomarker for drug sensitivity in pancreatic adenocarcinoma [51,52] and head and neck squamous cell carcinoma [48]. Our comprehensive pharmacogenomic assessment revealed a signi cant correlation between reduced expression of the NLRP1 gene in cancer patients and enhanced sensitivity to a spectrum of chemotherapeutic and targeted agents.…”
Section: Discussionmentioning
confidence: 62%
“…Conversely, diminished levels of NLRP1 increased the sensitivity of pancreatic cancer cells to ERK inhibitors [46]. Multi-omics analyses further reinforce the prospect of NLRP1 serving as a biomarker for drug sensitivity in pancreatic adenocarcinoma [51,52] and head and neck squamous cell carcinoma [48]. Our comprehensive pharmacogenomic assessment revealed a signi cant correlation between reduced expression of the NLRP1 gene in cancer patients and enhanced sensitivity to a spectrum of chemotherapeutic and targeted agents.…”
Section: Discussionmentioning
confidence: 62%
“…Similar to these studies, our study also carried out methods such as survival analysis, ROC and external cohort validation of PMSRPS, but it still has its advantages. First, after knowing the importance of subtyping based on molecular characteristics of cancer for improving clinical treatment decision-making, we did not directly use PRGs to establish a prognostic signature as many previous studies had done (84)(85)(86)(87)(88), but instead identified three stable pyroptosis molecular subtypes based on PRGs expression levels. By analysis, we found that different PRGclusters had different survival outcomes and immune cell infiltration manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…PLCG1, also called phospholipase C, gamma 1, is involved in the receptor tyrosine kinase-(RTK-)-mediated signal transduction pathway ( 47 ). A study found that PRGPI might serve as a prognostic biomarker for pancreatic cancer patients ( 48 ). Besides, numerous studies have proven the involvement of PLCG1-mediated inflammatory response in the pathogenesis of osteoarthritis and lung cancer ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%